Behavioural Analysis of a Nonlinear Mechanical System Using Transient Trajectories - Weber, Hans Ingo; Balthazar, José Manoel [UNESP]; Belato, Débora [UNESP] (Trans Tech Publications, 2003)
This work aims at a better comprehension of the features of the solution surface of a dynamical system presenting a numerical procedure based on transient trajectories. For a given set of initial conditions an analysis is made, similar to that of a return map, looking for the new configuration of this set in the first Poincaré sections. The mentioned set of I.C. will result in a curve that can be fitted by a polynomial, i.e. an analytical expression that will be called initial function in the undamped case and transient function in the damped situation. Thus, it is possible to identify using analytical methods the main stable regions of the phase portrait without a long computational time, making easier a global comprehension of the nonlinear dynamics and the corresponding stability analysis of its solutions. This strategy allows foreseeing the dynamic behavior of the system close to the region of fundamental resonance, providing a better visualization of the structure of its phase portrait. The application chosen to present this methodology is a mechanical pendulum driven through a crankshaft that moves horizontally its suspension point.
Keywords: Bifurcation; Nonlinear Dynamics; Phase Portrait Geometry; Stability; Phase potrait; Bifurcation (mathematics); Damping; Differential equations; Mathematical models; Polynomials; System stability; Nonlinear systems